Can immunosuppression be stopped after liver transplantation?. (July 2017) - Clavien, Pierre-Alain; Muller, Xavier; de Oliveira, Michelle L; Dutkowski, Philipp; Sanchez-Fueyo, Alberto
Summary: Liver transplantation has improved dramatically over the past three decades, mainly as a result of advances in surgical techniques and management of post-transplant complications. The focus has now turned towards rescuing additional organs in the face of scarce organ supply, or prevention of long-term toxicity associated with immunosuppression. The liver appears to be privileged in terms of immune tolerance, with a low incidence of antibody-mediated rejection, which is in sharp contrast to other solid organ transplants, such as kidney, lung, and heart transplants. However, tolerogenic processes remain poorly understood, and strategies for complete drug withdrawal should be selected carefully to avoid graft rejection. In this Review, we summarise the current understanding of liver-specific immune responses and provide an outlook on future approaches.